2018
DOI: 10.3390/w11010032
|View full text |Cite
|
Sign up to set email alerts
|

Ecohydrological Changes and Resilience of a Shallow Lake Ecosystem under Intense Human Pressure and Recent Climate Change

Abstract: In this work we present the complicated situation of a faunistically and floristically valuable ecosystem of the Rakutowskie Lake wetlands complex, which is part of the Special Protection Area for Birds of “Błota Rakutowskie” (PLB40001) and “Błota Kłócieńskie” Habitats Directive Sites (PLH040031) included in the Natura 2000 network. Numerous ornithological observations have drawn our attention to the problem of rapidly progressing overgrowth of the lake and significant fluctuations in its water surface area. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The average sum of annual precipitation within the Płock basin and surrounding areas measured at three meteorological stations (Baruchowo, Brześć Kujawski, Duninów) was 523 mm, which is lower than average for Poland (about 600 mm) (Bartczak 2007;Bartczak et al 2019). The study area is located within the rain shadow (e.g., latitudinal zone of low precipitation (< 550 mm)) which extends from the eastern part of Poland through the center to the western borders of the country.…”
Section: Study Areamentioning
confidence: 96%
See 2 more Smart Citations
“…The average sum of annual precipitation within the Płock basin and surrounding areas measured at three meteorological stations (Baruchowo, Brześć Kujawski, Duninów) was 523 mm, which is lower than average for Poland (about 600 mm) (Bartczak 2007;Bartczak et al 2019). The study area is located within the rain shadow (e.g., latitudinal zone of low precipitation (< 550 mm)) which extends from the eastern part of Poland through the center to the western borders of the country.…”
Section: Study Areamentioning
confidence: 96%
“…Climate projections for Poland foresee warming in all seasons and changes in the distribution and quantity of precipitation (Szwed 2015). Analyses of climatic water balance (the difference between precipitation P and evapotranspiration E) conducted by Bartczak et al (2019) for the investigated area showed a negative trend for the years 1967-2015. The projected further decrease in the summer climatic water balance (Szwed et al 2010) may adversely affect shallow lake ecosystems, such as Lake Rakutowskie, causing increased vegetation overgrowth and transformation into wetland.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is particularly important to conduct paleoecological investigations in peatlands in order to study long-term environmental changes (Gauthier et al, 2019). Thanks to paleoenvironmental research, knowledge about reference conditions has improved enabling to perform successful restoration processes (Bartczak et al, 2019; Lamentowicz et al, 2019; Słowiński et al, 2019). Therefore, obtaining key information about the past evolution of peatland ecosystems is essential, including past hydrological conditions and past vegetation on the peatland and in its catchment (Dietze et al, 2019; Fiałkiewicz-Kozieł et al, 2016; Lamentowicz et al, 2019; Zawisza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Droughts that we currently observe, and predictions inspire to study disturbances and resilience of ecosystems. The long-term ecosystem monitoring (Bartczak et al, 2019; Lamentowicz et al, 2016; Marcisz et al, 2014; Słowińska et al, 2010) or experiment (Jassey et al, 2018; Rastogi et al, 2019; Reczuga et al, 2018; Samson et al, 2018) provide a short temporal look at a disturbance. In contrast, palaeoecological multiproxy studies provide a long-term perspective (Marcisz et al, 2016; Zawisza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%